Exogenous miRNAs from Moringa oleifera Lam. recover a dysregulated lipid metabolism - Roglia, Valentina; Potestà, Marina; Minchella, Alessandra; Bruno, Stefania Paola; Bernardini, Roberta; Lettieri-Barbato, Daniele; Iacovelli, Federico; Gismondi, Angelo; Aquilano, Katia; Canini, Antonella; Muleo, Rosario; Colizzi, Vittorio; et al. (Frontiers in Molecular Biosciences, 2022)
A balanced diet is critical for human health, and edible plants play an important role in providing essential micronutrients as well as specific microRNAs (miRNAs) that can regulate human gene expression. Here we present the effects of Moringa oleifera (MO) miRNAs (mol-miRs) on lipid metabolism. Through in silico studies we identified the potential genes involved in lipid metabolism targeted by mol-miRs. To this end, we tested the efficacy of an aqueous extract of MO seeds (MOES), as suggested in traditional African ethnomedicine, or its purified miRNAs. The biological properties of MO preparations were investigated using a human derived hepatoma cell line (HepG2) as a model. MOES treatment decreased intracellular lipid accumulation and induced apoptosis in HepG2. In the same cell line, transfection with mol-miRs showed similar effects to MOES. Moreover, the effect of the mol-miR pool was investigated in a pre-obese mouse model, in which treatment with mol-miRs was able to prevent dysregulation of lipid metabolism.